Efektivitas Sosialisasi Low Back Pain Sebagai Upaya Meningkatkan Pengetahuan Risiko Low Back Pain pada Kelompok Tani Mulyo Kecamatan Matesih - Nabylla Sharfina Sekar Nurriwanti; Rizqy Kartika Sari; Jordan Syah Gustav; Zainun Akbar Lathif; Jasmine Dwi Anggreany; Khairunnisa Aurel Widiya Haryanto (Jurnal Sains dan Kesehatan, 2024)
Indonesia is a country where the majority of its population works as farmers. One of the occupational health risks that can affect farmers is low back pain. An initial study, based on health data from the Matesih Health Center, found that many farmers in the area under the Matesih Health Center's jurisdiction reported complaints of low back pain. Therefore, efforts need to be made to reduce the risk of low back pain. The Mulyo Farmers' Group is one of the farmer associations in Gugur Village, Matesih District. Socialization is one of the efforts that can be made to increase knowledge about low back pain among the Mulyo Farmers' Group. This research used a pre-experimental design with a one-group pretest-posttest design. The sample consisted of 48 members of the Mulyo Farmers' Group, selected using simple random sampling. The statistical test used was the Wilcoxon Signed-Rank Test. The research activities included a pre-test, socialization about low back pain, and a post-test. The results showed that there was a significant difference in the level of knowledge before and after the socialization about low back pain in the Mulyo Farmers' Group.